Urartu Krallığı'nda Tarım ve Hayvancılık ile Krallığın Ekonomi Politikası* - (:unkn) unknown (My University, 2018)
Bu çalışmada Urartu Krallığı'nın sosyo-ekonomik yapısı, devletin tarım ve hayvancılıkla ilgili etkinliklerine dair arkeolojik ve yazılı veriler göz önünde bulundurularak incelenmektedir. Urartu krallık ekonomisinin temelini tarım ve hayvancılık oluşturmaktadır. Ayrıca askerî seferler sonucu elde edilen ganimetler, vergiler, ticaret ve madencilik de krallık ekonomisine önemli katkılar yapmıştır. Bu çalışmada ayrıca Urartu Krallığı'nın sosyo-ekonomik ve politik gelişiminin "erken yayılmacı", "kriz dönemi" ve "yeniden yapılanma ve reform" olmak üzere üç farklı gelişim evresi gösterdiği ifade edilmiştir.

In this study, the socio-economic structure of the Urartian kingdom is examined by considering the archaeological and written evidence of the state’s activities related to agriculture and animal husbandry. The state economy is based on agriculture and animal husbandry. Military campaign of Urartian kings also generated revenues in terms of booty and tribute for the state economy. Metallurgical and trade activities also made substantial contribution to the state economy. This study also proposed three different developmental stages for the socio-economic and political development of the Urartian kingdom: an ‘early expansionist’, a ‘crisis period’ and a ‘restructuring and reform’ period.
AGRICULTURE AND ANIMAL HUSBANDRY IN URARTIAN KINGDOM AND THE ECONOMIC ORGANISATION OF THE KINGDOM